Discrimination of Minority Ethnic Chinese in Film “Ngenest” by Ernest Prakarsa : A Sociolinguistics Study - Hasma Rahmat Gundala; Puspita Sari (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The title of the study is Discrimination Minority Ethnic Chinese In Film "NGENEST" By Ernest Prakarsa: A Sociolinguistics Study. The study aims to analyze and examine the kinds and reasons for discrimination against minority ethnic Chinese. The data in this study are utterances containing discrimination against minority ethnic Chinese in the “NGENEST” movie By Ernest Prakarsa. This analysis was conducted through qualitative data. The research instrument is the researcher “pribumi”. The data used is taken from the sites of the layarkaca21 (LK21). The theory used to analyze the kinds of discrimination is from Uli Parulian Sihombing and the theory used to analyze reasons is from Yahya. The findings indicated that there were five different types of discrimination, including discrimination based on social caste (20%), sex and gender discrimination (0%), discrimination against individuals with disabilities (0%), and prejudice against people with HIV/AIDS (0%). In addition, there are six reasons found, namely reasons for One's Psychological Defense Mechanism (20%), reasons for disappointment (20%), the reason for experiencing feelings of insecurity and low self-esteem (20%), the reason for the history (20%), reasons for the competition and exploitation of society (20%), and reason for the discrimination socialization pattern (0%).